Eternal Revision: Screen Adaptations of Gogol’s Texts in the 21st Century / Вечная ревизия. Экранизации гоголевских текстов в ХХI в. - Zorin Artem N. / Зорин А.Н.; Riasov Daniil L. / Рясов Д.Л.; Mohammed Wijdan A. / Мохаммед В.А. (Наука телевидения)
Post-Soviet era directors have been searching for the new aesthetic footholds in the images of Gogol’s works. Starting from pure satire denouncing the pre-revolutionary system, they have moved on to the absurdist grotesque. This was significantly influenced by the discoveries of Gogol scholars in the 1990s–2000s and the actualization of the interpretations of Gogol’s works created at the turn of the 19th–20th centuries, which were inconceivable for Soviet literary criticism Screen adaptations have been affected both directly—by theatrical productions of Gogol’s oeuvre, and indirectly—by a long tradition of stage appeals and directors’ decisions on his stories. The transfer of Gogol’s dramaturgy into the 21st century gave film directors and screenwriters the opportunity to maximize the relevance and social sensitivity of the plots. In the 21st century, the theme of an inspection as an image of the Last Judgment has been transformed into a semblance of a police detective. Most of the characters are related to the police or special services, to investigations, to real retribution. While for Gogol the idea of judgement lies in the moral plane, in post-Soviet interpretations it is usually associated with earthly requital, and an extremely explicit one, tailored to a crime TV series audience. Against such a background, Grigory Konstantinopolsky’s film adaptation of Dead Souls summarizes a decade of Gogol film interpretations. The story of Chichikov blatantly accumulates and travesties the previous tradition of presenting Gogol’s detective plots. The film actualizes the issue of a positive hero, the problem of memory transformation, and cinema’s responsibility to the society in the period of losing its literature-centeredness. The transformation of the spiritual and intimate life of Gogol’s contemporaries, which was the most important theme for the writer, was also updated in a number of motifs: the lack of foundations for understanding between loving people (Marriage, 2009), the displacement of traditional gender roles (Happy Ending, 2010), the privatization of national memory, and summing up the unformed aesthetics of the new Russian cinema by the “lost generation” of the ‘90s (Dead Souls, 2020). Режиссеры постсоветской эпохи искали новые эстетические опоры в образности Гоголя, переходя от чистой сатиры с обличением дореволюционной системы к абсурдистскому гротеску. Значительное влияние на это оказали гоголеведческие открытия 1990-х–2000-х гг. и актуализация трактовок творчества Гоголя рубежа ХIХ–ХХ вв., неприемлемых в советском литературоведении. Экранизации испытали как непосредственное влияние театральных постановок («Ревизор» Сергея Газарова), так и опосредованное — сложившейся к этому времени традиции сценических решений гоголевских сюжетов. Перенесение драматургии Гоголя на экран в ХХI в. дало режиссерам и сценаристам возможность максимальной актуализации и социальной заостренности сюжетов. Тема ревизии как образа Страшного суда в ХХI в. трансформировалась в подобие полицейского детектива. Большинство героев экранизаций в результате сценарной реинтерпретации оказывалось связано с полицией / спецслужбами, следствием, расследованием, с реальным возмездием. В постсоветских трактовках идея суда, лежащая для Гоголя в моральной плоскости, связывается с проблемой земного возмездия и возмездия предельно конкретного, рассчитанного на зрителя криминальных сериалов. На этом фоне итоговая для десятилетия кинопрочтений экранизация «Мертвых душ» Г. Константинопольского откровенно аккумулирует и травестирует предшествующую традицию представления гоголевских детективных сюжетов. Фильм актуализирует вопрос о положительном герое, проблеме трансформации памяти, ответственности кино перед обществом в период утраты литературоцентризма. Важнейшая для Гоголя тема неполноценности духовной жизни современника, его тотального одиночества также оказалась актуализирована в целом ряде мотивов, таких как: отсутствие основ для взаимопонимания любящих людей («Женитьба», 2009), смещение традиционных гендерных ролей («Счастливый конец», 2010), приватизация национальной памяти и подведение итогов неоформившейся эстетики нового русского кино «потерянным поколением» 1990-х («Мертвые души», 2020).